(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2005)
CIRTA (’’Construction Incrémentale des Réseaux de Petri à Termes Algébriques”) is a specification language endowing ECATNets (’’Extended Concurrent Algebraic Terms Nets”) [6][10] with modularity concepts to make them more suitable for real-world applications. This paper addresses the structuring mechanisms provided by CIRTA, for the design of complex concurrent systems. Two structuring techniques are presented. The first one relies on the usage of CIRTA modules which extend ECATNets with the concepts of interface nodes and composed-nodes. The second mechanism concerns with some structuring operations on CIRTA modules namely: importation, composition and renaming. The semantics of each CIRTA specification using these constructs is defined by giving the behavioral equivalent ECATNet.